ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN - Sulaeman, Karin Maulia; Ramdan, Asep Muhamad; Jhoansyah, Dicky (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
The purpose of this study is to analyze customer relationship management and customer value on customer loyalty. The author uses quantitative research methods with descriptive and associative approaches. The population used in this study were customers of PT KAI DAOP I Sukabumi Station. In this study, researchers used a purposive sampling technique. From the customer population of PT KAI Sukabumi, the researchers decided to use the Cochra formula, with a total of 385 samples. The data analysis technique used is the classical assumption test, multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficient and partial test (t test).The results showed that partially customer relationship management and customer value have an effect on customer loyalty. The contribution of the influence of customer relationship management variables and customer value on customer loyalty is 58.4%. While the remaining 41.6% is influenced by other variables outside the sales of this regression or variables that are not examined.